MEDIALNE WYKORZYSTYWANIE IGRZYSK OLIMPIJSKICH W BUDOWANIU TOŻSAMOŚCI NARODOWEJ WĘGRÓW - Nagy, László (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Since 2010 the Hungarian government has played a major political role in the development of sports, including football and the Olympic movement. Despite the lack of proper infrastructure, daily physical education classes were introduced in Hungarian schools. Across the country, significant sports projects are being realised. Among these, the building and reconstruction of stadiums are a priority. In the home village of the Hungarian Prime Minister, a stadium capable of accommodating 3500 spectators was also built, while the number of inhabitants of Felcsút is below 2000.The results of competitive sports are utilised for enhancing national pride and the achievements of the government in a way similar to the methods of the totalitarian political regime of the 20th century. During the 2016 Summer Olympics in Rio de Janerio, a Hungarian House was built, which was designed to popularise and support Hungary’s tender for organising the 2024 Olympic Games. Owing to a civil movement’s initiative to hold a referendum on the issue, the government withdrew the application at the beginning of 2017. The resistance to the Olympics on behalf opposition parties and partly of society was primarily caused by the growing corruption reaching the highest levels of political leadership.